2016
DOI: 10.1016/j.chb.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Facebook friends, subjective well-being, social support, and personality

Abstract: a b s t r a c tOffline social capital in the form of interpersonal networks is known to be associated with subjective well-being (SWB). In two studies run in the US (N ¼ 153) and Germany (N ¼ 187), we initially investigated whether the size of an individual's Facebook social network was associated with SWB and perceived social support. Objectively measured Facebook network size was positively associated with several measures of both self-and informant rated SWB but not with perceived social support. More perti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 60 publications
5
52
0
3
Order By: Relevance
“…A plethora of research studies have been conducted on Facebook from different facets. Several studies have demonstrated the influence of prolonged use of Facebook on the psychological characteristics (attitudes and behaviors) of users (Amichai-Hamburger & Vinitzky, 2010;Correa et al, 2010;Dickie & Meier, 2015;Hayes et al, 2015;Lönnqvist & große Deters, 2016;Ross et al, 2009;Ryan & Xenos, 2011;Sagioglou & Greitemeyer, 2014;Shen et al, 2015;Wilson, Fornasier, & White, 2010). Some other existing studies pinpoint the effect of Facebook media interaction between users (Brailovskaia & Bierhoff, 2016;Mendes, Furtado, Militao, & de Castro, 2015), and several other studies have been carried out to investigate the privacy, trust and security concerns on Facebook (Junior, Xavier, & Prates, 2014;Külcü & Henkoğlu, 2014;Saeri, Ogilvie, La Macchia, Smith, & Louis, 2014;Tsay-Vogel et al, 2016).…”
Section: Facebook Literature Reviewmentioning
confidence: 99%
“…A plethora of research studies have been conducted on Facebook from different facets. Several studies have demonstrated the influence of prolonged use of Facebook on the psychological characteristics (attitudes and behaviors) of users (Amichai-Hamburger & Vinitzky, 2010;Correa et al, 2010;Dickie & Meier, 2015;Hayes et al, 2015;Lönnqvist & große Deters, 2016;Ross et al, 2009;Ryan & Xenos, 2011;Sagioglou & Greitemeyer, 2014;Shen et al, 2015;Wilson, Fornasier, & White, 2010). Some other existing studies pinpoint the effect of Facebook media interaction between users (Brailovskaia & Bierhoff, 2016;Mendes, Furtado, Militao, & de Castro, 2015), and several other studies have been carried out to investigate the privacy, trust and security concerns on Facebook (Junior, Xavier, & Prates, 2014;Külcü & Henkoğlu, 2014;Saeri, Ogilvie, La Macchia, Smith, & Louis, 2014;Tsay-Vogel et al, 2016).…”
Section: Facebook Literature Reviewmentioning
confidence: 99%
“…School-related social support has positive on subjective well-being among teenagers have been proved, and the teacher's support is significant to the school satisfaction of students (Reddy, 2003 [52] ; Tian a, 2015 [53] ). The social network work and online communication can be regarded as social sources which is one kind of the social support, and there are studies to demonstrate that online behavior influences real-life behavioral, social capital also has been mentioned in social media studies, social media use has a positive effect on subjective well-being and social capital (Bumsoo, Yonghwan, 2017 [54] ; Lonnqvist, Deters, 2016 [55] ). The involvement in a group or class also influences the college student's selfefficacy, self-esteem mediated the relationship between leadership strengths and life satisfaction is proved (Weber, Ruch, 2013 [56] ).…”
Section: Social Support and Subjective Well-beingmentioning
confidence: 99%
“…Además de los contactos, permite fortalecer las relaciones (Boyd y Ellison, 2007;Ellison, Steinfield y Lampe, 2007;Johnston, Tanner, Lalla y Kawalski, 2013;Lönnqvist y Deters, 2016;Wilcox y Stephen, 2013).…”
unclassified